The Effect of Coarse Aggregate Size On Pervious Concrete Mixture - Erwin, Sutandar; Asep, Supriyadi; M, Indrayadi; Ferry, Juniardi; Syahrudin, Syahrudin (Jurnal Teknik Sipil, 2022)
Along with the development progress in Indonesia, it causes the reduction of green areas. Coupled with the lack of public awareness of the environment is a problem that must be considered. Pervious concrete that be as one of the solutions in pavement construction, concrete sheet piles, retaining walls is a product that can be considered successfully in meeting expectations as an environmentally friendly construction. For road pavement, pervious concrete must have a strength of 30 MPa. Therefore, there is a need for research for the mix design of pervious concrete using the ACI 522R-10 Report on Pervious Concrete method with an initial design compressive strength of 25 MPa. The method is to vary the coarse aggregate used in the pervious concrete mixture. In this research, it is divided into 5 variations to find a mixture that is in accordance with the plan or which exceeds the initial plan, and its permeability still meets the requirements for pervious concrete. Testing of the specimens includes the volume weight test, compressive strength, split tensile strength, modulus of elasticity of concrete, porosity, absorption, and permeability. From the research, the results of the volume weight of pervious concrete are 1,974.14 - 2,187.83 kg/m3 that pervious concrete is included in the lightweight concrete group due to it has a weight below 2,200 kg/m3 . The average compressive strength of pervious concrete is 20.089 "“ 46.978 MPa. The value of the split tensile strength of pervious concrete is 8,968-19,127 MPa. The average value of porosity is between 8,307 "“ 13,097%. The average value of absorption is between 3.452 "“ 5.444%. The average value of the permeability is between 0.0025-0.487 cm3/sec. From this research, it can be concluded that the use of different coarse aggregates size will produce pervious concrete with different compressive strengths. The compressive strength with aggregate size 0.5x0.5 without sieving, it closed to the initial plan of 27.72 MPa, whereas the highest compressive strength is for a mixed aggregate size of 1/1 and 0.5/0.5 cm with sieving that the compressive strength achieved 46.978 MPa